Gama Melon Parfum, a Potential Melon Genotype Tolerant of Salinity Stress - Nugroho, Giri; Chikmawati, Tatik; Sartika, Dian; Yusuf, Adib Fakhruddin; Putro, Karso Suryo; Latifah, Vida Rahma; Daryono, Budi Setiadi; Wibowo, Anjar Tri; Nurhayati, Awik Puji Dyah; Meitha, Karlia; Miftahudin, Miftahudin (UI Scholars Hub, 2025)
Melona, Tacapa Gold, and Gama Melon Parfum are novel Melon genotypes that have been introduced for cultivation in the saline-prone coastal region of Bocor Beach, Kebumen, Central Jawa. Elevated salt concentrations in the area pose challenges, impacting yield. The potential of these new genotypes for saline land remains unexplored. This study aimed to assess the morphophysiological and molecular responses of these genotypes to salinity stress. Seeds were germinated in cocopeat and ABmix 3000 solution and treated with 220 mM NaCl until harvest. The analysis included morphology, chlorophyll content, proline accumulation, malondialdehyde levels, and gene expression were analyzed. After 1 week of salinity stress, the results showed reduced plant height, leaf number, stomatal density, percentage of opened stomata, and width and length of leaves. The malondialdehyde, proline, and root-shoot dry mass ratio increased. The expression of CSD1-1, P5CR, and late embryogenesis abundant genes increased under salinity treatment. Gama Melon Parfum exhibits salt tolerance, as indicated by higher P5CR gene expression, proline accumulation, and leaf-relative water content. P5CR gene expression, proline accumulation, and leaf-relative water content are valuable indicators of salt tolerance for assessing melon genotypes.